Development of Integrated Spiritual, Moral, and Scientific (SMS) Islamic Education Instructional Materials for High School Students - Ernawati, Luluk; Kholis, Nur; Zainiyati, Husniyatus Salamah (LETIGES, 2025)
In many schools, conventional approaches to Islamic Education remain limited by an emphasis on rote memorisation, reducing impact on students' social behaviour and insufficient opportunities for critical thinking. To address these challenges, this study developed Integrated Spiritual, Moral, and Scientific (SMS) Islamic Education instructional materials designed to foster holistic learning among high school students. Employing the Borg and Gall research and development (R&D) model, which comprises ten systematic stages, the study engaged teachers and students from four senior high schools in Gresik, East Java. The development process involved needs assessment, material design, expert validation, pilot testing, revisions, and large-scale field implementation. Data was collected using a combination of interviews, questionnaires, observations, achievement tests, and documentation. Qualitative data were analysed using descriptive methods, while quantitative data underwent statistical analysis to assess effectiveness and validity. The findings demonstrated that the SMS instructional materials achieved high content validity, with expert ratings averaging above 94%, and showed strong practical feasibility, with over 90% of teachers and students responding positively. The experimental group using the SMS materials significantly improved learning outcomes, outperforming the control group by 26% in post-test scores. Students reported greater motivation and understanding, while teachers observed enhanced classroom engagement and deeper internalisation of spiritual and moral values. Despite these promising results, the study was limited to a single region and semester, and the instruments used to assess spiritual and moral outcomes require further validation. Future research is recommended to explore longitudinal impacts, extend the application to more diverse educational contexts, refine assessment tools, and integrate digital analytics to personalise SMS-based instruction.